Regional brain susceptibility to neurodegeneration: what is the role of glial cells? - Andrea Beatriz Cragnolini; Giorgia Lampitella; Assunta Virtuoso; Immacolata Viscovo; Fivos Panetsos; Michele Papa; Giovanni Cirillo (Neural Regeneration Research, 2020)
The main pathological feature of the neurodegenerative diseases is represented by neuronal death that represents the final step of a cascade of adverse/hostile events. Early in the neurodegenerative process, glial cells (including astrocytes, microglial cells, and oligodendrocytes) activate and trigger an insidious neuroinflammatory reaction, metabolic decay, blood brain barrier dysfunction and energy impairment, boosting neuronal death. How these mechanisms might induce selective neuronal death in specific brain areas are far from being elucidated. The last two decades of neurobiological studies have provided evidence of the main role of glial cells in most of the processes of the central nervous system, from development to synaptogenesis, neuronal homeostasis and integration into, highly specific neuro-glial networks. In this mini-review, we moved from in vitro and in vivo models of neurodegeneration to analyze the putative role of glial cells in the early mechanisms of neurodegeneration. We report changes of transcriptional, genetic, morphological, and metabolic activity in astrocytes and microglial cells in specific brain areas before neuronal degeneration, providing evidence in experimental models of neurodegenerative disorders, including Parkinson’s and Alzheimer’s diseases. Understanding these mechanisms might increase the insight of these processes and pave the way for new specific glia-targeted therapeutic strategies for neurodegenerative disorders.